PH20 is not expressed in murine CNS and oligodendrocyte precursor cells. Issue 3 (23rd February 2017) - Marella, Mathieu; Ouyang, Joe; Zombeck, Jonathan; Zhao, Chunmei; Huang, Lei; Connor, Robert J.; Phan, Kim B.; Jorge, Michael C.; Printz, Marie A.; Paladini, Rudolph D.; Gelb, Arnold B.; Huang, Zhongdong; et al.
Abstract: Objective: Expression of Spam1 /PH20 and its modulation of high/low molecular weight hyaluronan substrate have been proposed to play an important role in murine oligodendrocyte precursor cell (OPC) maturation in vitro and in normal and demyelinated central nervous system (CNS). We reexamined this using highly purified PH20. Methods: Steady‐state expression of mRNA in OPCs was evaluated by quantitative polymerase chain reaction; the role of PH20 in bovine testicular hyaluronidase (BTH) inhibition of OPC differentiation was explored by comparing BTH to a purified recombinant human PH20 (rHuPH20). Contaminants in commercial BTH were identified and their impact on OPC differentiation characterized. Spam1 /PH20 expression in normal and demyelinated mouse CNS tissue was investigated using deep RNA sequencing and immunohistological methods with two antibodies directed against recombinant murine PH20. Results: BTH, but not rHuPH20, inhibited OPC differentiation in vitro. Basic fibroblast growth factor (bFGF) was identified as a significant contaminant in BTH, and bFGF immunodepletion reversed the inhibitory effects of BTH on OPC differentiation. Spam1 mRNA was undetected in OPCs in vitro and in vivo; PH20 immunolabeling was undetected in normal and demyelinated CNS. Interpretation: We were unable to detect Spam1 /PH20 expression in OPCs or in normal or demyelinated CNS using the most sensitive methods currently available. Further, "BTH" effects on OPC differentiation are not due to PH20, but may be attributable to contaminating bFGF. Our data suggest that caution be exercised when using some commercially available hyaluronidases, and reports of Spam1 /PH20 morphogenic activity in the CNS may be due to contaminants in reagents.